1999
DOI: 10.1897/1551-5028(1999)018<2316:pticom>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Identifying Causes of Maldevelopment Induced in Xenopus by Pond Water and Sediment Extracts From Minnesota, Usa

Abstract: In previously conducted laboratory studies with the South African clawed frog (Xenopus laevis), pond water and sediment samples collected from various sites in Minnesota, USA, were demonstrated to have the potential to induce a variety of developmental abnormalities, including early embryo-larval maldevelopment, abnormal limb development, and disruption of metamorphosis. The results of exposure of X. laevis to suspect pond water and sediment samples supported the hypothesis that these samples were capable of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…Thus, based on this study, longer-term developmental processes seemingly are more likely to be affected by sulfonylurea herbicides. These findings are not necessarily surprising, because the amphibian endocrine system has recently been identified as a significant target for many environmental toxicants [3,[22][23][24]. The sensitivity of this stage of development can be attributed to the importance and myriad of functions the endocrine system, particularly the thyroid axis, plays during metamorphosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, based on this study, longer-term developmental processes seemingly are more likely to be affected by sulfonylurea herbicides. These findings are not necessarily surprising, because the amphibian endocrine system has recently been identified as a significant target for many environmental toxicants [3,[22][23][24]. The sensitivity of this stage of development can be attributed to the importance and myriad of functions the endocrine system, particularly the thyroid axis, plays during metamorphosis.…”
Section: Discussionmentioning
confidence: 97%
“…Because the thyroid axis, including thyroid hormones and thyroid hormone receptors, is of paramount importance in the maturation of frogs, thyroid dysfunction is capable of producing a myriad of deleterious effects. For example, resorption of the tail, secondary anatomical characteristics, morphogen activity, development of the limbs, and maturation of juvenile skin to that of adult frogs are at least partially controlled by the thyroid axis [3,[22][23][24]. Thus, the possibility of larvae with severe thyroid dysfunction surviving in the wild is slim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Test systems successfully applied in EDA were presented including the frog embryo teratogenesis assay with Xenopus laevis (FETAX) [106], fish embryo test applying eggs of Salmo trutta [107] and Oryzias latipes [108].…”
Section: Aquatic Toxicitymentioning
confidence: 99%
“…in Canada [134]) raised the requirement to identify the causing compounds. This was attempted by Fort et al [106] who identified and qualitatively confirmed propylthiourea, the carbamate fungicide maneb and the pyrethroid insecticide permethrin as important contributors to frog teratogenicity.…”
Section: Aquatic Toxicantsmentioning
confidence: 99%